SKRINING FITOKIMIA, AKTIVITAS ANTIOKSIDAN DAN TOKSISITAS AKUT INFUSA BIJI DAN PERIKARP BUAH OLAE (Etlingera calophrys) - Salam, Diah Astari; Sabandar, Carla Wulandari; Ummul Fausiah; Harni Sartika Kamaruddin; Megawati; Nisrina Muslihin (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2025)
Olae (Etlingera calophrys), an endemic of Southeast Sulawesi, Indonesia, is traditionally used as a culinary spice and medicine, yet remains scientifically underexplored. This study investigated the phytochemical composition, antioxidant activity, and acute toxicity of infusion extract from the seeds and fruit pericarp. Phytochemical screening was performed using specific color reagents, antioxidant activity was evaluated with the 2.2-diphenyl-1-picrylhydrazyl (DPPH) method, and acute toxicity was assessed by the Brine Shrimp Lethality Test (BSLT) against Artemia salina. The seed infusion contained alkaloids and phenolics, while the pericarp infusion contained tannins and phenolics. Antioxidant testing revealed very strong radical scavenging activity, with SC₅₀ values of 0.05 g/100 mL (seeds) and 0.04 g/100 mL (pericarp). Toxicity testing indicated no significant toxicity, with LC₅₀ values of 1740 g/100 mL (seeds) and 2510 g/100 mL (pericarp). These findings suggest that infusion extract of E. calophrys possess strong antioxidant potential and are safe for use, supporting their prospective application as natural antioxidant sources.